GAMBARAN MANAJEMEN TEMPAT TIDUR RAWAT INAP KELAS 3 DI RSUD Dr. M. SOEWANDHIE SURABAYA - Nurul Jannatul Firdausi; Agus Aan Adriansyah (UNUSA Press, 2018)
National Health Insurance (JKN) has encouraged utilization of Inpatient Department (IPD).The highest improvement by poor who funded by JKN-PBI scheme. Unbalancing supply and demandare potentially making queuesand effect to prolonged waiting times. The study aims to define bedmanagement in the 3rd class IPD of RSUD. Dr. M. Soewandhie Surabaya. Type of study wasobservasional-descriptive with cross sectional design. Study was conducted in The 3rd Class IPD ofRSUD. Dr. M Soewandhi beginning on June to August 2018. Sample was patients who have beendecided to discharged from IPD. Sampling technique by simple random sampling. The sample sizewere 104 patients. Data collection by observing process of patients discharge to preparation ofinpatient rooms (cleaning and put on the linen). Analysis dat in narrative and supported by graphsand tables. The results: the peak time of patient discharge and patient admission has gap about 4hour time. Room booking is centralized at Administration, but updating data is constrained due togathering information by telephone to nurses in IPD. Cycle time to provide a bed for 165 minutes(Takt Time = 52 minutes). The longest process is waiting for patient discharge and cleaning services.Provision of inpatient rooms still long, so the hospital management needs to improve patient flow,administration and information when patient discharge untill room cleaning.